'Plastic' border: Ceuta, behind and beyond the walls. (1st January 2014) - Bernes, Laure-Anne
While strengthening territorial discontinuity and crafting the image of Fortress Europe, the consolidation of the barrier function of Ceuta's border conceals or blurs local dynamics and policing practices. A simplistic account of local dynamics would thus state that, despite the ostensible hyper-activation of the barrier function of the border, the borderline is both open and closed, hard and soft . Classical dichotomies are clearly rendered too clumsy a tool to comprehend borders and grasp the significance of permeability. Using the single case-study method, this paper puts forward the notion of plasticity in an attempt to take a step back and displace the analytical lens from the result of border controls (the variable degree of permeability) to the very process and social mechanisms that structure it. Plasticity takes stock of the "constant state of becoming of the border" (Kaiser, 2012). This not only entails the 'dyadic interplay' between controllers and users (Coplan, 2012) socially inscribed in the borderland, but also the spatially dispersed and transient nature of wider bordering capabilities.